Optimizing C-Type Natriuretic Peptide and Receptor Expression Analysis with Droplet Digital™ PCR: Advancing Biomarker Discovery for Brugada Syndrome? - Cabiati, Manuela; Vozzi, Federico; Persiani, Elisa; Piacenti, Marcello; Rossi, Andrea; Sgalippa, Agnese; Cecchettini, Antonella; Solarino, Gianluca; Zucchelli, Giulio; Mazzocchetti, Lorenzo; Notarstefano, Pasquale; Guiducci, Letizia; et al. (Biomolecules (Basel, Switzerland), 2025)
Brugada syndrome (BrS) is a cardiac disease associated with characteristic ECG abnormalities and a heightened risk of sudden cardiac death, especially in young individuals with structurally normal hearts. The primary aim of this study was to highlight, for the first time, the potential of using droplet digital PCR (ddPCR), a highly sensitive method, to detect C-type natriuretic peptide (CNP) and its receptors, NPR-B and NPR-C, expression in BrS. Whole-blood samples from 12 subjects with type 1 BrS and 12 controls were analyzed. CNP expression was detectable and lower in BrS patients than in the controls, although not significantly. NPR-B and NPR-C expression was significantly reduced in the same patients (p ≤ 0.05). Strong correlations were observed between CNP and NPR-B (p = 0.01) and NPR-C (p < 0.0001), as well as between NPR-B and NPR-C (p = 0.0002). Body weight correlated with CNP (p = 0.02), NPR-B (p = 0.03), and NPR-C (p = 0.02); meanwhile, NPR-B expression was related to height (p = 0.05). This study is the first to analyze CNP expression and its specific receptors using ddPCR technology, showing for the first time their presence and activation in individuals with BrS. Although further research is needed to clarify CNP-related mechanisms, these findings offer a valuable starting point for exploring its role in BrS.